Nghiên cứu chế tạo vật liệu nanocompozit trên cơ sở nhựa epoxy DER 331 và nanoclay. Phần 1. Nghiên cứu chế độ phân tán nanoclay vào nhựa epoxy, ảnh hưởng của hàm lượng nanoclay đến tính chất cơ học của vật liệu. - Quyền, Nguyễn Công; Chương, Bùi; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2014)
In this paper, the influence of dispersion methods on dispersion degree of nanoclay in epoxy matrix was studied. The dispersion degree of nanoclay was evaluated by various, method, namely XRD, viscosity measurement and TEM techniques. The results showed that high speed stirring (2000 rpm) may create the interchalated structure of nanoclay in matrix: the d-spacing of I28E increased from 23.33 Å to 38.02 Å, and for I30E from 26.71 Å to 40.12 Å after 10 hours stirring. The combination of high speed stirring with ultra sonication still more increases the dispersion efficiency: the d-spacing of both studied nanoclay was increasing almost 2 times. The presence of nanoclay increased fracture toughness of nanocomposites compared to neat epoxy. Keywords: Dispersion, nanoclay, epoxy resin.